Залежність фільтраційної здатності нирок від фенотипу хронічної серцевої недостатності, показників систолічної та діастолічної функції серця - Сиволап, Віталій Вікторович; Лисенко, Владислав Андрійович; Syvolap, V. V.; Lysenko, V. A.; Сыволап, В. В.; Лысенко, В. А. (My University, 2021)
Недостатньо вивчено питання змін фільтраційної здатності нирок залежно від структурно-геометричної та функціо-нальної перебудови серця при різних фенотипах хронічної серцевої недостатності (ХСН), порушень систолічної та діастолічної функції лівого шлуночка (ЛШ).Мета роботи – дослідити взаємозв’язок змін фільтраційної здатності нирок у хворих на хронічну серцеву недостатність ішемічного ґенезу залежно від фенотипу, показників систолічної та діастолічної функції серця.Матеріали та методи. У дослідження залучили 87 (45 чоловіків, 42 жінки) хворих на ХСН ішемічного ґенезу із си-нусовим ритмом, II А–Б стадії, II–IV ФК за NYHA, яких поділили на 2 групи. У 1 групу включили хворих зі зниженою (<45 %) фракцією викиду (ФВ) лівого шлуночка (n = 57; 59,6 % чоловіків), у 2 – хворих на ХСН зі збереженою ФВ лівого шлуночка (n = 30; 36,6 % чоловіків). Групи хворих зіставні за віком, статтю, зростом, вагою, площею поверхні тіла. Доплер-ехокардіографічне дослідження виконали на апараті Esaote MyLab Eight (Італія). Швидкість клубочкової фільтрації (ШКФ) оцінювали за допомогою формул CKD-EPІ, MDRD і Cockcroft-Gault.Результати. Ниркову дисфункцію за CKD-EPІ зареєстрували у 72 % хворих на ХСН, за MDRD – у 66,7 %, за Cockcroft-Gault – у 52,6 %. Від типів ХСН залежали тільки показники рівня креатиніну крові (p = 0,011) та розрахунковий показник швидкості клубочкової фільтрації за Cockcroft-Gault (p = 0,047). ШКФ за всіма застосованими формулами (СKD-EPI, MDRD, Cockcroft-Gault) залежала від віку (r = -0,42; p = 0,001), зросту (r = 0,28; p = 0,08), ваги (r = 0,31; p = 0,004), площі поверхні тіла (r = 0,33; p = 0,002). Встановили прямий кореляційний зв’язок рівня креатиніну з індексом маси міокарда ЛШ, що розрахована за формулою Penn Convention, але не виявили залежність рівня креатиніну та ШКФ від типів геометрії ЛШ. Доведено наявність оберненої кореляційної залежності між ФВ ЛШ і рівнем креатиніну крові (r = -0,3172; p = 0,003), між умістом креатиніну та S lat (r = -0,531; р = 0,006), прямий кореляційний зв’язок визначили між S lat і CKD-EPІ (r = 0,5586; p = 0,004), MDRD (r = 0,6254; p = 0,001), Cockcroft-Gault (r = 0,4043; p = 0,045).Висновки. При ХСН ішемічного ґенезу зі зниженою ФВ лівого шлуночка спостерігали вираженіше порушення філь-траційної здатності нирок, ніж у хворих на ХСН зі збереженою ФВ лівого шлуночка. Між ФВ лівого шлуночка та вмістом креатиніну крові виявили зворотний кореляційний зв’язок (r = -0,3172; p = 0,003). Зниження показника систолічної швидкості руху латеральної частини фіброзного кільця мітрального клапана асоціюється зі зниженням фільтраційної здатності нирок за вмістом креатиніну (r = -0,531; р = 0,006), ШКФ за формулами CKD-EPІ (r = 0,5586; p = 0,004), MDRD (r = 0,6254; p = 0,001), Cockcroft-Gault (r = 0,4043; p = 0,045) у хворих на ХСН ішемічного ґенезу обох фенотипів. У хворих на ХСН ішемічного ґенезу обох фенотипів індекс маси міокарда, що розрахована за формулою Penn Convention, корелює з концентрацією креатиніну крові (r = 0,95; p= 0,003). У хворих на ХСН ішемічного ґенезу рестриктивний тип діастолічного наповнення лівого шлуночка асоціюється з вірогідним підвищенням рівня креатиніну крові на 14 % (p = 0,03) порівняно з пацієнтами з діастолічною дисфункцією ЛШ за типом порушення релаксації. The issue of changes in the filtration capacity of the kidneys depending on the structural-geometric and functional remodeling of the heart in different phenotypes of chronic heart failure, disorders of systolic and diastolic function of the left ventricle remains insufficiently studied.The aim of this work: to investigate the relationship between changes in the filtration capacity of the kidneys in patients with chronic heart failure of ischemic genesis depending on the phenotype, indicators of systolic and diastolic cardiac function.Materials and methods. After an informed consent was signed, 87 patients (men – n = 45, women – n = 42) with CHF of ischemic genesis with sinus rhythm, stage II A–B, II–IV functional class NYHA, who were divided into 2 groups, were involved in the study. Group 1 included patients with reduced (<45 %) left ventricular ejection fraction (HFrEF) (n = 57; 59.6 % men), group 2 – patients with CHF with preserved left ventricular ejection fraction (HFpEF) (n = 30; 36.6 % men). Patient groups were comparable in terms of age, sex, height, weight, and body surface area. Doppler echocardiographic examination was performed using the Esaote MyLab Eight (Italy). Glomerular filtration rate (GFR) was assessed using the CKD-EPI, MDRD, and Cockcroft-Gault formulas. Results. Renal dysfunction was registered in patients with CHF in 72 % of cases when calculated using the CKD-EPI formula, 66.7 % using the MDRD formula and 52.6 % using the Cockcroft-Gault formula. Only indicators of blood creatinine level (P = 0.011) and the calculated indicator of glomerular filtration rate according to Cockcroft-Gault (p = 0.047) depended on the types of CHF. GFR for all applied formulas (СKD-EPI, MDRD, Cockcroft-Gault) depended on age (r = -0.42; P = 0.001), height (r = 0.28; P = 0.08), weight (r = 0.31; P = 0.004), body surface area (r = 0.33; P = 0.002). A direct correlation between the creatinine level and the LV myocardial mass index, calculated using the Penn Convention formula, was established, however, the dependence of the creatinine level and GFR on the types of LV geometry was not revealed. The presence of an inverse correlation between LVEF and blood creatinine level (r = -0.3172; P = 0.003), be-tween creatinine content and S lat (r = -0.531; Р = 0.006), a direct correlation between S lat and CKD-EPI (r = 0.5586; P = 0.004), MDRD (r = 0.6254; P = 0.001), Cockcroft-Gault (r = 0.4043; P = 0.045).Conclusions. In chronic heart failure of ischemic genesis with reduced left ventricular ejection fraction, a more pronounced impairment of the filtration capacity of the kidneys than in chronic heart failure patients with preserved left ventricular ejection fraction is observed. An inverse correlation was established between the LV EF and the blood creatinine level (r = -0.3172; P = 0.003). A decrease in the systolic velocity of movement of the lateral annulus fibrosus of the mitral valve is associated with a decrease in the filtration capacity of the kidneys in terms of creatinine level (r = -0.531; P = 0.006), GFR according to the CKD-EPI (r = 0.5586; P = 0.004), MDRD (r = 0.6254; P = 0.001), Cockcroft-Gault (r = 0.4043; P = 0.045) in patients with CHF of ischemic genesis of both phenotypes. In patients with CHF of ischemic genesis of both phenotypes, the myocardial mass index, calculated according to the Penn Convention, correlates with the blood creatinine content (r = 0.95; P = 0.003). In patients with CHF of ischemic genesis, the restrictive type of diastolic filling of the left ventricle is associated with a significant increase in blood creatinine levels by 14 % (P = 0.03) compared with patients with diastolic LV dysfunction by the type of relaxation disord. Остается недостаточно изученным вопрос изменений фильтрационной способности почек в зависимости от структур-но-геометрического и функционального ремоделирования сердца при различных фенотипах хронической сердечной недостаточности (ХСН), нарушений систолической и диастолической функции левого желудочка (ЛЖ).Цель работы – исследовать взаимосвязь изменений фильтрационной способности почек у больных хронической сердечной недостаточностью ишемического генеза в зависимости от фенотипа, показателей систолической и диа-столической функции сердца.Материалы и методы. В исследование включены 87 (45 мужчин, 42 женщины) больных ХСН ишемического генеза с синусовым ритмом, II А–Б стадии, II–IV ФК по NYHA, которых разделили на 2 группы. В 1 группу вошли больные со сниженной (<45 %) ФВ левого желудочка (n = 57; 59,6 % мужчин), во 2 группу – больные ХСН с сохраненной ФВ левого желудочка (n = 30; 36,6 % мужчин). Группы больных сопоставимы по возрасту, полу, росту, весу, площади поверхности тела. Допплер-эхокардиографическое исследование выполнено на аппарате Esaote MyLab Eight (Италия). Скорость клубочковой фильтрации (СКФ) оценивали с помощью формул CKD-EPI, MDRD и Cockcroft-Gault.Результаты. Почечная дисфункция зарегистрирована у 72 % больных ХСН при расчете по формуле CKD-EPI, 66,7 % – по формуле MDRD, 52,6 % – по формуле Cockcroft-Gault. От типов ХСН зависели только показатели уровня креатинина крови (p = 0,011) и расчетный показатель скорости клубочковой фильтрации по Cockcroft-Gault (p = 0,047). СКФ по всем примененными формулам (СKD-EPI, MDRD, Cockcroft-Gault) зависела от возраста (r = -0,42; p = 0,001), роста (r = 0,28; p = 0,08), веса (r = 0,31; p = 0,004), площади поверхности тела (r = 0,33; p = 0,002). Установлена прямая корреляционная связь уровня креатинина с индексом массы миокарда ЛЖ, рассчитанной по формуле Penn Convention, но не установлена зависимость уровня креатинина и СКФ от типов геометрии ЛЖ. Доказано наличие обратной корреляционной зависимости между ФВ ЛЖ и уровнем креатинина крови (r = -0,3172; p = 0,003), между содержанием креатинина и S lat (r = -0,531; р = 0,006), прямая корреляционная связь отмечена между S lat и CKD-EPI (r = 0,5586; p = 0,004), MDRD (r = 0,6254; p = 0,001), Cockcroft-Gault (r = 0,4043; p = 0,045).Выводы. При ХСН ишемического генеза со сниженной ФВ левого желудочка отмечено более выраженное наруше-ние фильтрационной способности почек, чем у больных ХСН с сохраненной ФВ левого желудочка. Между ФВ левого желудочка и уровнем креатинина крови установлена обратная корреляционная связь (r = -0,3172; p = 0,003). Сни-жение показателя систолической скорости движения латеральной части фиброзного кольца митрального клапана ассоциируется со снижением фильтрационной способности почек по уровню креатинина (r = -0,531; р = 0,006), СКФ по формуле CKD-EPI (r = 0,5586; p = 0,004), MDRD (r = 0,6254; p = 0,001), Cockcroft-Gault (r = 0,4043; p = 0,045) у больных ХСН ишемического генеза обоих фенотипов. У больных ХСН ишемического генеза обоих фенотипов индекс массы миокарда, рассчитанной по формуле Penn Convention, коррелирует с содержанием креатинина крови (r = 0,95; p = 0,003). У больных ХСН ишемического ге-неза рестриктивный тип диастолического наполнения левого желудочка ассоциируется с достоверным повышением уровня креатинина крови на 14 % (p = 0,03) по сравнению с больными с диастолической дисфункцией ЛЖ по типу нарушения релаксации.
Dependence of renal filtration capacity on the phenotype of chronic heart failure, indicators of systolic and diastolic heart function
Зависимость фильтрационной способности почек от фенотипа хронической сердечной недостаточности, показателей систолической и диастолической функции сердца
Сиволап В. В. - ORCID ID: 0000-0001-9865-4325; Лисенко В. А. - ORCID ID: 0000-0001-7502-0127
Keywords: ниркова дисфункція; хронічна серцева недостатність; систолічна функція серця; діастолічна функція серця; renal dysfunction; chronic heart failure; systolic heart function; diastolic heart function; почечная дисфункция; хроническая сердечная недостаточность; систолическая функция сердца; диастолическая функция сердца